POTENSI ANGGREK INDONESIA DI TENGAH PANDEMI COVID-19 - Nova Anggraeni (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Orchid plants are plants that have the most species among other plants. According to O'Byrne there are 17,000 – 35,000 species and an estimated 750 -850 genera of orchids spread throughout the world. The various types of orchids in terms of shape, beauty and uniqueness make consumers attractive to orchids. Orchids also have added value when they are able to produce an aroma. In addition, crosses known as hybrid orchids also have their own market share. This is because the results of hybrid orchids that continue to grow have led to high public interest in maintaining orchids. Orchids are widely used as religious ceremonies, decorations, greeting flowers and home decorations. The Covid-19 pandemic that has hit the world as well as Indonesia from 2020 until now has made several business sectors experience problems in sales. The government-initiated stay at home movement has hampered several sectors. However, this is actually profitable in the business of trading orchids and their supporting components. People are prohibited from leaving the house and must be busy with various activities so as not to get bored. The gardening movement is one option. For those who do not like gardening with soil, orchid plants are an alternative to pass the time. So the sale of orchids has also increased along with changes in people's behavior patterns during the pandemic. On the demand side, Indonesian floricultural commodities are quite attractive to both the domestic and global markets. Indonesia has the potential to meet the needs of the global market for floriculture because it is supported by an agro-climate as a tropical country. This indicates that the orchid business must determine the type of orchid that is feasible and has good sales potential.